THE COMPUTER SIMULATOR-CONTROLLER FOR LEARNING SIGN AND SYMBOLIC MEANS OF PHYSICS (Journal of Information Technologies in Education (ITE), 2012)
The promising application of information technology for learning sign and symbolic means of physics is proposed and theoretically proved in this article. This direction is connected with the idea of training students the presentation of information in different forms.
Keywords: computer simulator-controller; deployment of bilingual mental processes; sign and symbolic means